Mentoring Hand-Written Batik Techniques for Youth in Jerukgamping Village to Foster Interest in Culture-Based Entrepreneurship - Sumartini Rahayu; Miftahillah Miftahillah (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2026)
Hand-drawn batik is an Indonesian cultural heritage with aesthetic, philosophical, and economic value, yet it faces the challenge of artisan regeneration at the village level. This community service program aimed to assist youth in Jerukgamping Village, Krian Subdistrict, Sidoarjo Regency, in mastering basic hand-drawn batik techniques and fostering culture-based entrepreneurial interest. The program used the Asset-Based Community Development approach through the stages of Discovery, Dream, Design, Define/Deliver, and Destiny. The activities included local asset mapping, canting and coloring practice, strengthening understanding of motif values, introducing a simple business plan, and assisting product documentation and digital marketing. The results showed that the youth participants were able to recognize batik as a cultural product with economic value, understand the basic stages of hand-drawn batik production, produce initial works, and begin preparing product portfolios for promotion. The program also strengthened collaboration among youth, local artisans, village officials, and the higher education institution. Therefore, hand-drawn batik assistance can serve as a youth empowerment model that connects cultural preservation with the strengthening of the local creative economy.